Names of Palm Sunday in the tradition of the Western Church - Sieradzki, Andrzej (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The subject of analysis in this article is the names of the sixth Sunday of Lent (Palm Sunday), which functioned over the centuries in the official church language. Analyses are basically limited to Latin names. The way to identify this Sunday in vernacular languages is cited only in exceptional cases. In determining the motivation for the various names, I use direct testimony from the anonymous text Sermones dominicales IV. In Dominica Palmarum, which dates from the early Middle Ages. The research conducted shows that the names of Sunday were motivated in different semantic areas. They were related either directly to Gospel events or to worship, penitential practices, baptismal rites and the theological interpretation of the holiday itself. In each of these areas, certain elements are highlighted, which are the direct motivation for the name, giving it its proper meaning. These elements are always specific in nature. These include objects (e.g., palm tree, tree branches), e.g., Dominica Palmarum, persons (e.g., penitent, awaiting baptism), e.g., Dominica Reconciliationem, and actions related to the situation (e.g., singing, head washing), e.g., Dominica Capitilavii. This way of categorization shows that it was done from a colloquial perspective. The only exceptions in this regard are names of the Passion Sunday type, which cover the entire event with their scope, rather than its isolated element. However, they are the product of theological thought.